Tree-ring management : take the long view and grow your business slowly - Tsukakoshi, Hiroshi, 1937-; Larrabee, Hart (Tokyo, Japan : Japan Publishing Industry Foundation for Culture, 2015)
"Hiroshi Tsukakoshi is the chairman of a kanten manufacturer that is far from the bustle of Tokyo amid the natural beauty of Nagano prefect ure. His desire has been to build the kind of company that makes its em ployees happy and makes a contribution to society by doing so. His phil osophy is to take the long view, growing his business slowly and steadi ly through "tree-ring management." "Over the last 20 years, no one has left the company because they were unhappy," Tsukakoshi declares. His u nique management principles include such ideas as "rapid growth is the enemy" and "the essence of management is creating fans." His approach h as resulted in rising sales and profits for half a century since the co mpany's founding, and his company welcomes a steady stream of visiting executives and analysts from major corporations, including Murata Manuf acturing and the Toyota Group. Chairman Tsukakoshi's philosophy of seek ing steady growth over the long term will enlighten businesspeople arou nd the world about a better way to manage corporations." --
"An English translation of Risutora nashi no nenrin keiei (Tree-Ring Management with No Downsizing), originally published by Kobunsha in 20 09 and revised in 2014"--Page 3.
Keywords: Corporate culture -- Japan; Industrial management -- Japan; Work environment -- Japan